2021
DOI: 10.51847/hzxov7ry2b
|View full text |Cite
|
Sign up to set email alerts
|

Leading Professionally Diverse Workgroups of Healthcare Professionals for Improving Quality of Care

Abstract: The purpose of this paper is to unfold the internal dynamics of a workgroup of healthcare professionals and to identify leadership behaviors that can enhance the benefits of professional diversity to improve the quality of care. The present study explores the recent literature on leadership, professional diversity within workgroups of healthcare professionals, and their performance outcomes especially the quality of care. The finding reveals that the sub-group categorization is salient diversity generated proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…With specific reference to the healthcare industry, several scholars (Bradley, 2020;Gomez & Bernet, 2019;Koopmans et al, 2018;Rosen et al, 2018;Sfantou et al, 2017;Smith et al, 2018;Yousaf et al, 2021) explained that diversity can functionally improve both financial performance and patient care satisfaction.…”
Section: Diversity Pracɵces and Innovaɵonmentioning
confidence: 99%
See 1 more Smart Citation
“…With specific reference to the healthcare industry, several scholars (Bradley, 2020;Gomez & Bernet, 2019;Koopmans et al, 2018;Rosen et al, 2018;Sfantou et al, 2017;Smith et al, 2018;Yousaf et al, 2021) explained that diversity can functionally improve both financial performance and patient care satisfaction.…”
Section: Diversity Pracɵces and Innovaɵonmentioning
confidence: 99%
“…With specific reference to the healthcare industry, several scholars (Bradley, 2020; Brimhall, 2019; Gomez & Bernet, 2019; Koopmans et al, 2018; Rosen et al, 2018; Sfantou et al, 2017; Smith et al, 2018; Yousaf et al, 2021) explained that diversity can functionally improve both financial performance and patient care satisfaction. Their various studies revealed that healthcare professionals from different disciplines and levels can enhance the quality of care, improve performance and reduce the mortality rates in the hospitals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The psychological safety climate provides an arena where group members can develop a perception that the group has acceptability of their views, which can accelerate the process of information sharing. Inclusive behaviors of leaders are essential for creating a psychological safety climate within groups for improving quality of care [ 45 ], because they engage with staff from different disciplines and hierarchal levels, and encourage true participation within healthcare settings [ 2 , 66 ]. It enables them to elaborate on care-related information within the group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quality of care is considered a performance indicator for healthcare professionals working in groups [ 1 ]. These workgroups, whether working in conventional formations or controlled combinations of professional silos, become multiprofessional in nature and ineluctably acquire the characteristics of professional diversity [ 2 ] due to the presence of two or more individuals with professionally diverse backgrounds [ 3 ]. Based on this premise, the quality of care is mainly attributed to the communication of different care-related perspectives and informational resources among these individuals [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation